Fuzzy evaluation model of software project performance based on grey clustering analysis - Wei Wang (Sir Syed University Research Journal of Engineering and Technology, 2020)
This paper introduces the general principles that should be followed in project performance evaluation: through the analysis of the main factors affecting software project performance evaluation, it provides a guiding principle for the construction of project performance evaluation index system including software project characteristics and project characteristics. The empirical study shows that the model can effectively evaluate software project performance and knowledge. It provides decision support information for software organizations to formulate risk aversion strategies, improve project performance level and other risk factors.